2022
DOI: 10.1016/j.ebiom.2021.103792
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant materials & applications inspired by food technologies

Abstract: Food science and technology have a fundamental and considerable overlap with medicine, and many clinically important applications were borne out of translational food science research. Globally, the food industry -through various food processing technologies -generates huge quantities of agro-waste and food processing byproducts that retain a significant biochemical potential for upcycling into important medical applications. This review explores some distinct clinical applications that are fabricable from foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Benefits of fermentation have been reported by Metchnikoff (1907) 115 years ago, and the intensive current scientific interest in the human microbiome (e.g., oral microbiota, gut-brain axis) is evidence for the importance and potential of fermentation processes and products. Fermentation processes, which also attracted medical, biomedical, and research communities (Choi et al, 2022;Cui et al, 2022;Żółkiewicz et al, 2020), have been shown to have very low water and carbon footprints or land use requirements compared to conventional food production, and the effectiveness of post-biotics especially anti-inflammatory, immunomodulatory, and anti-cancer properties has been presented (Żółkiewicz et al, 2020). Effects of food fermentation include increased bacteriocin genetic potential against pathogens and removal of non-nutrients; partial degradation of toxic or harmful substances; and generation of biologically active components such as anti-oxidants, antimicrobial, anti-allergic, or anti-inflammatory compounds (Breza-Boruta et al, 2022;Kelly et al, 2022;Şanlier et al, 2019).…”
Section: Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits of fermentation have been reported by Metchnikoff (1907) 115 years ago, and the intensive current scientific interest in the human microbiome (e.g., oral microbiota, gut-brain axis) is evidence for the importance and potential of fermentation processes and products. Fermentation processes, which also attracted medical, biomedical, and research communities (Choi et al, 2022;Cui et al, 2022;Żółkiewicz et al, 2020), have been shown to have very low water and carbon footprints or land use requirements compared to conventional food production, and the effectiveness of post-biotics especially anti-inflammatory, immunomodulatory, and anti-cancer properties has been presented (Żółkiewicz et al, 2020). Effects of food fermentation include increased bacteriocin genetic potential against pathogens and removal of non-nutrients; partial degradation of toxic or harmful substances; and generation of biologically active components such as anti-oxidants, antimicrobial, anti-allergic, or anti-inflammatory compounds (Breza-Boruta et al, 2022;Kelly et al, 2022;Şanlier et al, 2019).…”
Section: Fermentationmentioning
confidence: 99%
“…Benefits of fermentation have been reported by Metchnikoff (1907) 115 years ago, and the intensive current scientific interest in the human microbiome (e.g., oral microbiota, gut‐brain axis) is evidence for the importance and potential of fermentation processes and products. Fermentation processes, which also attracted medical, biomedical, and research communities (Choi et al., 2022; Cui et al., 2022; Żółkiewicz et al., 2020), have been shown to have very low water and carbon footprints or land use requirements compared to conventional food production, and the effectiveness of post‐biotics especially anti‐inflammatory, immunomodulatory, and anti‐cancer properties has been presented (Żółkiewicz et al., 2020).…”
Section: Resilient Food Technologiesmentioning
confidence: 99%
“…Minimal studies are available involving edible plant-based pork rinds that accurately mimic the original texture, appearance, and mouthfeel of natural pork rinds. There is a significant overlap between food science and medicine as a multidisciplinary field [ 7 ]. In the medical field, gels are commonly used to simulate skin for wound management, cosmetic surgery [ 8 ], and in vitro simulation experiments [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation is a modern engineering technology means, using some specific functions of microorganisms for biological modification of useful products . In recent years, fermentation technology has been widely used in the pharmaceutical industry, chemical industry, and environmental science. , It also plays a growingly important role in the food industry . Food materials including WB abound with bioactive compounds, which mostly covalent-bind with biomacromolecules such as lignin, cellulose, and protein.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It also plays a growingly important role in the food industry. 16 Food materials including WB abound with bioactive compounds, which mostly covalent-bind with biomacromolecules such as lignin, cellulose, and protein. They can be released from the complex structures by the enzymes secreted by microorganisms during fermentation.…”
Section: ■ Introductionmentioning
confidence: 99%